Entre medicamentos psiquiátricos e gestão da vida: a produção da autonomia na saúde mental pela gestão autônoma da medicação - Cavalheiro, Fernanda dos Santos (2020)
WiththeBrazilianPsychiatricReform, Mental Health hasbeenconcernedwithovercomingandcriticizingthebiomedicaland hospital-centeredmodel, focusedondiseaseanddrugtreatment, togenerateservices in a comprehensive, territorial care network, promotingtheemancipationofsubjects. The AutonomousMedication Management (GAM) guide, aninstrumentcreatedbyalternative mental healthservices in Quebec-Canada, arrives in Brazil in 2009 as a strategyto mobilize pluralityofpositionsandchoicesregardingdrugtreatment, accessto social rights , as well as theneedtosharedecisionsandresponsibilitiesbetweenprofessionalsandusers. Therefore, thisworkhadthe general objectiveofdevelopingthe processes ofautonomyproductionofferedbythe GAM strategy in mental healthservices. As specificobjectives, analyzethe GAM userandmoderatorguidesandtheirstrategiesoffered for theproductionofautonomyandwaysoflife for mental healthusers; tomaphowthepromotionofautonomy in GAM establishesrelationshipsofknowledgeandpower in the use ofpsychiatricdrugs in the management ofthelivesof mental healthusersandtounderstandhowthepromotionofautonomy in GAM produceseffects in thedeinstitutionalizationofthese mental healthservices, basedontheparticipation in GAM groups. Thisproposalhadtwomethodologicalmomentsofresearch.The firstpart as a documentaryresearch, wherepublicationsofelectronicdatabasesthatworkonthethemeof GAM andtheUserandmoderatorguidesweregathered as a discursive corpus, problematizingtheenunciativeeffectswithregardtopublicpolicyandtreatmentoffers. in mental health. For theanalysisofthisresearch, wetookthethoughtof Michel Foucault regardingtheexplicitprogramanddiscussedthattheguides are technicalproductions, whichencourage a programthatbringstogetherautonomouswaysofliferecommendedbythe RPB. In thesecondmoment, a participatoryinterventionresearchwascarried out, withtheparticipationoftheresearcher in two GAM groups, being a PsychosocialCare Center (CAPS) and a Family Health Strategy (ESF). The data productionperiod for thesesurveyswasMarchand August 2019. The instrumentusedwasthefielddiary. Afterthecompletionofeachgroup, ananalysiswasproduced, ofFoucauldianinspiration, being in thefirstfield (CAPS), fromthetheater it waspossibletoworkonissuesrelatedtotheproductionofautonomyandtheeffectsof GAM; in thefield (ESF), fromthe meeting of a groupofwomen, weseektodealcollectivelywithmicropolitics in everydaylife, togivethesewomenaccessto new existentialterritories. Thismaster'sthesisisconcludedwiththesethreechapters in theformofarticles, whichcorrespondtothreemomentsofresearchthat GAM madepossible as a strategy in a policyexercisethatfocusedontheproductionofgreaterdegreesofautonomyandcitizenshipofthesub jectsinvolved in theresearch.